2017
DOI: 10.1007/s11356-017-9944-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, sources and risk assessment of PAHs in bottom sediments

Abstract: The aims of the study were to investigate the concentration, sources and ecological risk of PAHs (polycyclic aromatic hydrocarbons) in bottom sediments collected from nine reservoirs located in south-eastern Poland. The concentration of ∑PAHs in sediments ranged from 150 to 33,900 μg kg . The total PAH concentration in the bottom sediments was arranged in the following order: Rybnik > Rzeszów > Brzóza Królewska > Brzóza Stadnicka > Besko > Chechło > Ożanna > Głuchów > Narożniki. BAP was the major compound in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 51 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…The bottom sediments of the Chańcza reservoir contained on average 35.4 g, the Besko reservoir—18.2 g, the Zesławice reservoir—15.8 g, the Rzeszów reservoir—23.5 g, the Ożanna reservoir—31.3 g TOC/kg d.m. (Baran and Tarnawski 2013; Baran et al 2017). The content of extracted carbon (Cext) in a mixture of Na 4 P 2 O 7 + NaOH with a concentration of 0.1 mol dm −3 exhibited less diversification in comparison with the TOC content ( V % = 86) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The bottom sediments of the Chańcza reservoir contained on average 35.4 g, the Besko reservoir—18.2 g, the Zesławice reservoir—15.8 g, the Rzeszów reservoir—23.5 g, the Ożanna reservoir—31.3 g TOC/kg d.m. (Baran and Tarnawski 2013; Baran et al 2017). The content of extracted carbon (Cext) in a mixture of Na 4 P 2 O 7 + NaOH with a concentration of 0.1 mol dm −3 exhibited less diversification in comparison with the TOC content ( V % = 86) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sediments from the Rzeszów reservoir had high concentrations of PAHs (III class). The reservoir is under strong human pressure associated with industry, long-range transport of PAHs and local agriculture, which causes severe erosion of the land (Koniarz et al 2015 ; Bartoszek et al 2015 ; Baran et al 2017 ). Bartoszek et al ( 2015 ) showed that the greatest impact on the quality of bottom sediments is connected with the presence of BAP.…”
Section: Resultsmentioning
confidence: 99%
“…Organic carbon is an important parameter governing the distribution and adsorption of PAHs in bottom sediments (Dahle et al 2003 ; Wang et al 2013 ). A strong relationship between PAH concentrations and organic matter content or clay fraction in bottom sediments is often observed (Oros and Rosa 2004 ; Khairy et al 2009 ; Lubecki and Kowalewska 2010 ; Baran et al 2017 ). Moreover, relationships among the individual metals were significantly, positively correlated with one another and with the PAHs (except Cd) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations